'The first dragon to slay': unpacking Kenya's war on drugs. Issue 148 (2nd April 2016) - Dimova, Margarita
Abstract : Kenya faces the challenge of policing not only drug smuggling through its territory, but a sprawling local market dominated by heroin. The government is enthusiastically embracing the global 'war on drugs' discourse, propped by external actors' assistance and insistence. Guided by these developments, this article analyses Kenya's local war on drugs using ethnographic material from immersive fieldwork in Nairobi and Mombasa. The aim is to decode local political actors' engagement in the international drug control regime and its impact on everyday perceptions of Kenyan state authority. As such, this article provides an alternative explanation of the mechanics of Kenyan drug markets and the role some government officials play in (controlling) them.